Main Dulu, Paham Gizi Kemudian: Wordwall sebagai Media Pembelajaran Triguna Makanan pada Anak Sekolah Dasar - Isma Meiranda; Sulistiyono, Priyo (NUTRIASIK: Jurnal Terapan Gizi dan Pangan Fungsional Kesehatan, 2026)
The problem of undernutrition and overnutrition in school-age children in Indonesia is still high and has an impact on physical, mental, and intellectual growth. Low nutritional knowledge, including the concept of food trigunas (energy, builders, and regulators), is one of the indirect factors in the occurrence of malnutrition. This study aims to determine the increase in knowledge of food triguna after nutrition education using Wordwall educational game media in grade V students of SDN 1 Dompyong Wetan. The study used a pre-experimental design of one group pre-test–post-test without a control group. The sample totals 42 students. Knowledge was measured using an 18-item questionnaire before and three days after the intervention. The results showed that before the intervention 92.9% of students were in the category of lack of knowledge. After education, 81.0% of students were in the good category, 14.3% adequate, and 4.8% lacking. All students experienced an increase in scores with an average pre-test of 29.4 to 89.7 in the post-test, with an average increase of 60.3 points. In conclusion, Wordwall is effective in increasing knowledge of food triguna in elementary school students and has the potential to be an interesting nutrition learning medium.